Defining and transforming local migration policies: a conceptual approach backed by evidence from Germany. Issue 13 (3rd October 2021) - Schammann, Hannes; Gluns, Danielle; Heimann, Christiane; Müller, Sandra; Wittchen, Tobias; Younso, Christin; Ziegler, Franziska
ABSTRACT: What are the factors that drive municipalities to become active in the field of migration and migration-related diversity? Based on qualitative data from 126 German municipalities, this article proposes a new conceptual framework that allows for larger-scale comparisons and enables theory building on policy (in)activity at the local level. Setting the scene, the article discusses various theoretical approaches and empirical findings from the literature by using a heuristic of four categories of factors: institutional framework (e.g. competencies, discretionary spaces, multilevel governance), structural conditions (e.g. urbanity/rurality, socioeconomic conditions); local discourses (i.e. narratives creating a local space of possibilities), and local key actors (e.g. mayors, street-level bureaucrats). Empirically assessing the relative importance of these factors, the article focusses on local integration plans. In the German context, a municipality usually establishes an integration plan to actively control the outcome of integration processes, e.g. by orchestrating local stakeholders or allocating resources. Thus, the development of an integration plan can be used as a proxy for a municipality's appetite to strategically engage with migration and migration-related diversity. As a result, the article proposes the 'ISDA framework of local migration policymaking', which distinguishes between 'defining factors' (institutional framework, structural conditions) and 'transformative factors' (discourses, actors).